Conceptual design of a model for the creation and development of youth symphony orchestras in Bulgaria - Terzieva-Angelova, Svetlina (Young Scientific Music and Dance Forum : Conference with international participation, 2021)
Numerous studies have shown that orchestral activities are extremely beneficial for the academic, cognitive, social and emotional growth of young people. The idea that these activities can revitalize, expand and enrich the musical education in Bulgaria and contribute to the social inclusion and integration of young people at risk inspired me to explore the practices and models of youth orchestras in Venezuela, England and USA. After analyzing the collected information on the experience of UK’s National Plan For Music Education and the elements of the Venezuelan El Sistema, I hereby proposed a Model for the Development and Growth of Youth Symphony Orchestras in Bulgaria, which is practical and can be efficiently implemented. The recent Pre-school and School Education Act of 2016 provides opportunities for this Model to be implemented in Bulgarian schools, allowing students to receive comprehensive musical education by introducing group training on musical instruments, ensembles and orchestras.